Glycine by MR spectroscopy is an imaging biomarker of glioma aggressiveness. Issue 7 (14th February 2020) - Tiwari, Vivek; Daoud, Elena V; Hatanpaa, Kimmo J; Gao, Ang; Zhang, Song; An, Zhongxu; Ganji, Sandeep K; Raisanen, Jack M; Lewis, Cheryl M; Askari, Pegah; Baxter, Jeannie; Levy, Michael; et al.
Abstract: Background: High-grade gliomas likely remodel the metabolic machinery to meet the increased demands for amino acids and nucleotides during rapid cell proliferation. Glycine, a non-essential amino acid and intermediate of nucleotide biosynthesis, may increase with proliferation. Non-invasive measurement of glycine by magnetic resonance spectroscopy (MRS) was evaluated as an imaging biomarker for assessment of tumor aggressiveness. Methods: We measured glycine, 2-hydroxyglutarate (2HG), and other tumor-related metabolites in 35 glioma patients using an MRS sequence tailored for co-detection of glycine and 2HG in gadolinium-enhancing and non-enhancing tumor regions on 3T MRI. Glycine and 2HG concentrations as measured by MRS were correlated with tumor cell proliferation (MIB-1 labeling index), expression of mitochondrial serine hydroxymethyltransferase (SHMT2), and glycine decarboxylase (GLDC) enzymes, and patient overall survival. Results: Elevated glycine was strongly associated with presence of gadolinium enhancement, indicating more rapidly proliferative disease. Glycine concentration was positively correlated with MIB-1, and levels higher than 2.5 mM showed significant association with shorter patient survival, irrespective of isocitrate dehydrogenase status. Concentration of 2HG did not correlate with MIB-1 index. A high glycine/2HG concentration ratio, >2.5, was strongly associated with shorter survival ( P < 0.0001). GLDC and SHMT2 expression were detectable in all tumors with glycine concentration, demonstrating an inverse correlation with GLDC. Conclusions: The data suggest that aggressive gliomas reprogram glycine-mediated one-carbon metabolism to meet the biosynthetic demands for rapid cell proliferation. MRS evaluation of glycine provides a non-invasive metabolic imaging biomarker that is predictive of tumor progression and clinical outcome. Key Points: 1. Glycine and 2-hydroxyglutarate in glioma patients are precisely co-detected using MRS at 3T. 2. Tumors with elevated glycine proliferate and progress rapidly. 3. A high glycine/2HG ratio is predictive of shortened patient survival.